Singular logarithmic potentials and peratization - Aly, H. H.; Riazuddin; Zimerman, A. H. (American Physical Society (APS), 1964)
Logarithmic singular potentials are considered to test the applicability of the peratization technique. It is shown that if one sums up the leading singular terms in each order of the perturbation series no finite results can be obtained. © 1964 The American Physical Society.